A case of successful yoga prana vidya energy healing treatment of contact dermatitis caused by Holigarna ferruginea Marchand - Nanduri, Venkata Satyanarayana; Nayak, Leelavathi (International Journal of Research in Dermatology, 2023)
Contact dermatitis is a rash or a condition that makes skin red or inflamed with rashes and pain after direct contact with an allergen or an irritant such as soap, cosmetics, fragrances, jewellery and plants. This paper presents a case of Holigarna ferruginea Marchand induced allergic contact dermatitis successfully healed using yoga prana vidya (YPV) healing protocols. This paper uses a case study method collecting patient data before and after healing, and details of YPV intervention applied by trained certified healers for treating this patient. After one day healing, the patient's body temperature became normal. After 2 days of healing, rashes and itching reduced. After further 5 days of healing, the blister on the patient's right hand also completely healed. As an integrated holistic system, the YPV system of healing has been found to be a less expensive modality without the use of any medications and without touching the patient. The successful treatment of contact dermatitis using YPV techniques opens potential avenues for applying these techniques for numerous other skin ailments. Further research is recommended.